Histology of PFO-associated stroke thrombus compared to iliofemoral deep vein thrombus: an explorative study. - Immens, M. H. M.; Stam, M.; Dippel, D. W. J.; Nijeholt, G. J. Lycklama à; van der Worp, H. B.; Jenniskens, S.; van Rijn, M. J.; de Leeuw, F. E.; Cate, T. J. F.ten; van Beusekom, H. M. M.; Tuladhar, Anil M. (Neuroradiology, 2025)
Purpose: A patent foramen ovale (PFO) is as a cause of thrombo-embolic stroke. It is thought that the thrombus originates from the venous circulation, although this has never been proven. The histological composition of the thrombus might help to identify its origin. The aim of this exploratory pilot study is to compare the histological composition of thrombi of patients with PFO-associated stroke with venous thrombi from patients with iliofemoral deep venous thrombosis (DVT). Methods: We retrieved thrombi from the MR CLEAN Registry, a Dutch nationwide, multicenter, prospective registry of patients who underwent endovascular treatment for ischemic stroke. Furthermore DVT thrombi were obtained as fully anonymous waste material and analyzed retrospectively. Results: Thrombi were available for three patients treated for PFO-associated stroke and four patients treated for DVT. The thrombi of patients with PFO-associated stroke contained less red blood cells (RBC) and more fibrin and platelets (Fib + Plt) than those with DVT (30.2% vs. 91.3% RBC and 67.4% vs. 8.5% Fib + Plt). The PFO-associated stroke thrombi were most comparable to thrombi from the same cohort classified as cardioembolic (RBC 25.8% and 67.1% Fib + Plt). As this is a descriptive histological analysis, no definitive comparisons between different thrombi can be made. Conclusion: We observed that the composition of the three thrombi from patients with PFO-associated stroke differs from that of the four DVT thrombi in our cohort. Prospective studies are needed to determine whether thrombi in PFO-associated stroke are all similar in composition and share a similar pathophysiology with venous thrombi.